PENERAPAN TEKNIK PERKUATAN STRUKTUR RANGKA ATAP BAJA UNTUK MENINGKATKAN KUALITAS BAHAN AJAR DI BENGKEL KONSTRUKSI BAJA - Dedi Budi Setiawan Setiawan; Rifqi Aulia Abdillah; Supriyo Supriyo; Arif Subakti Ariyanto; Nur Setiaji Pamungkas (Politeknik Negeri Semarang, 2026)
The roof frame is a structural element that supports the roof load and ensures thesafety and stability of the building. According to Abdillah et al. (2024), damage tothe roof frame can impact other components. For example, if the roof frame sags,the roof covering can loosen, causing leaks. These leaks can affect the ceiling,causing mold and, in the worst case, collapse. Therefore, reinforcement is needed torestore the reliability of the damaged roof truss structure. The purpose of roof truss reinforcement techniques is to increase the load capacity of the steel roof truss, reduce deformation, and minimize the potential for structural failure. The method used in this research is a case study method. A model of the damaged steel roof truss structure will be created, followed by repairs and load testing. The repair technique that can be applied to the damaged components of the roof truss structure that sags can use the method of thickening the steel profile and replacing the sagging profile.The results of the study showed that repairs using the profile thickening method can withstand a load of 534 kg and require a cost of Rp 407,754, while repairs using the profile replacement method can withstand a load of 628 kg and require a cost of Rp 492,905. The most effective repair technique to be applied to damaged roof truss structures that are sagging is the profile thickening method, because this method has almost the same strength as the profile replacement method, but the profile thickening method requires cheaper implementation costs and the repair method is easier.